2018
DOI: 10.1136/bmjgh-2018-001168
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping public hospitals: an agenda for reform in Asia and the Pacific

Abstract: Hospitals in the Asia‐Pacific today face the ‘triple aim’ challenge, proposed by the Institute for Healthcare Improvement, of how to improve quality of care and population health, while at the same time controlling healthcare costs. Yet, pursuing these challenges in combination is presently a remote prospect for many hospitals and, indeed, in a majority of countries in the region. The roles and functions of the public hospital sector within local health systems need redefinition and reform in the context of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…It is the responsibility of management, policymakers, and medical experts to change public hospitals going forward. 10 Problems are piling up for healthcare organizations these days for two main reasons: first, it's getting harder and harder to satisfy an increasingly "aware" and demanding user; and second, organizations need to restructure internally to stay up with the lightning-fast changes happening in technology and approach. Increasing complexity and doctors' abilities won't guarantee a company's most basic need: to provide customers with what they want.…”
Section: Discussionmentioning
confidence: 99%
“…It is the responsibility of management, policymakers, and medical experts to change public hospitals going forward. 10 Problems are piling up for healthcare organizations these days for two main reasons: first, it's getting harder and harder to satisfy an increasingly "aware" and demanding user; and second, organizations need to restructure internally to stay up with the lightning-fast changes happening in technology and approach. Increasing complexity and doctors' abilities won't guarantee a company's most basic need: to provide customers with what they want.…”
Section: Discussionmentioning
confidence: 99%
“…37 In the health sector, policies and laws have important influences on PPP, 11,56 and both regulations and guidelines have an impact on treatment management, 57 institutional forms in providing services, 58 and leadership stability. 59 In his study of collaboration between government and NGOs, Seddoh 60 found that policy is the third key factor after communication and structure, which is considered a significant influence on collaboration success.…”
Section: Governance and Policy Frameworkmentioning
confidence: 99%
“…Kedua dengan melakukan investasi dalam inovasi sistem melalui peningkatan sistem manajemen rumah sakit yang berkualitas dan didukung dengan tenaga professional yang berkualitas. Ketiga dengan melakukan reorientasi kompetensi tenaga Kesehatan dan keterampilan yang sesuai dengan kondisi saat ini (Gauld et al, 2018). Pada umumnya persalinan SC memiliki cost yang lebih tinggi dibandingkan persalinan normal sehingga menghasilkan profitabilitas yang tinggi terhadap rumah sakit meskipun menurut Healthcare Organization bahwa tujuan utama rumah sakit bukanlah pada profit nya.…”
Section: Dari Ketiga Peran Tersebut Peran Organisasi Profesi Yang Pal...unclassified